Polysaccharide‐Coated PCL Nanofibers for Wound Dressing Applications. Issue 12 (29th September 2014) - Croisier, Florence; Atanasova, Ganka; Poumay, Yves; Jérôme, Christine
<x xml:space="preserve">Abstract</x> Polysaccharide‐based nanofibers with a multilayered structure are prepared by combining electrospinning (ESP) and layer‐by‐layer (LBL) deposition techniques. Charged nanofibers are firstly prepared by electrospinning poly(ε‐caprolactone) (PCL) with a block‐copolymer bearing carboxylic acid functions. After deprotonation of the acid groups, the layer‐by‐layer deposition of polyelectrolyte polysaccharides, notably chitosan and hyaluronic acid, is used to coat the electrospun fibers. A multilayered structure is achieved by alternating the deposition of the positively charged chitosan with the deposition of a negatively charged polyelectrolyte. The construction of this multilayered structure is followed by Zeta potential measurements, and confirmed by observation of hollow nanofibers resulting from the dissolution of the PCL core in a selective solvent. These novel polysaccharide‐coated PCL fiber mats remarkably combine the mechanical resistance typical of the core material (PCL)—particularly in the hydrated state—with the surface properties of chitosan. The control of the nanofiber structure offered by the electrospinning technology, makes the developed process very promising to precisely design biomaterials for tissue engineering. Preliminary cell culture tests corroborate the potential use of such system in wound healing applications.